Application of Naphthalene Acetic Acid and Gibberellic acid: Their effects on Plant Physiological Characteristics of wax apple - Mohammad Moneruzzaman, Khandaker (2016)
The physiological characteristics study was conducted to investigate the effects of napthalene acetic acid (NAA) and gibeberellic acid (GA3) on plant physiological characteristics of Syzygium samarangense (wax apple) var. jambu madu. Different concentration was used in NAA and GA3 treatments where NAA at 10, 20 and 40 mg/L and GAJ at 20, 40 and 80 mg/L. In GA3 treatment, the result shown that application of 40 mg/L concentration gives the best result while, 10 mg/L and 20 mg/L treatments were the best concentration for NAA application to improve the plant physiological characteristics of Syzygium samarangense leaves. In addition, GA3 treatment had shown significant effect on new leaf length, petiole length, chlorophyll b, carotenoid content and stomata! conductance. NAA treatments had shown significant effects on petiole length, chlorophyll content (SPAD),chlorophyll b, carotenoid content and photosynthetic rate of leaf.